2020
DOI: 10.3390/su12229750
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cleaning Frequency of Photovoltaic Modules on Power Losses in the Desert Climate

Abstract: Dust accumulation on the photovoltaic (PV) surface decreases the solar radiation penetration to the PV cells and, eventually, the power production from the PV system. To prevent dust-based power losses, PV systems require frequent cleaning, the frequency of which depends on the geographical location, PV integration scheme, and scale of the PV power plant. This study aims to measure the drop-in radiation intensity, as well as power output, due to dust and to determine the optimal time interval for PV cleaning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Proper estimation of when to start cleaning of solar panels is a compromise between gross costs of cleaning the panels and how much reduction in efficiency of solar panels can be tolerated. Shah et al [154] studied the optimal time interval for PV cleaning in the UAE climate. This study revealed that the output power of the panels that remain uncleaned for 3 months decreased by 13% compared with the panels that were cleaned daily.…”
Section: Effect Of the Cleaning Frequency On The Efficiency Of The Pa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Proper estimation of when to start cleaning of solar panels is a compromise between gross costs of cleaning the panels and how much reduction in efficiency of solar panels can be tolerated. Shah et al [154] studied the optimal time interval for PV cleaning in the UAE climate. This study revealed that the output power of the panels that remain uncleaned for 3 months decreased by 13% compared with the panels that were cleaned daily.…”
Section: Effect Of the Cleaning Frequency On The Efficiency Of The Pa...mentioning
confidence: 99%
“…4) It takes less time to decay compared with hydrophilic coatings. 5) Depends on rainfall 6) High initial costs in case of large-scale PV systems perform the cleaning cycle for the installed PV systems in the MENA region on a weekly or biweekly basis [26,37,57,61,[154][155][156][157]. On the other hand, the majority of the PV systems in Europe are installed in rainy green regions, and the optimum pattern for cleaning is less frequent than that in the MENA and the Far East regions.…”
Section: Super Hydrophobic Surfacementioning
confidence: 99%
“…The drop in electric power compared to a daily cleaned reference PV module was 3%, 5% 7%, and 13% for 10 days, 20 days, 1 month, and 3 months respectively [58]. AL-Housani et al…”
Section: Monthsmentioning
confidence: 94%
“…The accumulation of dust on the surfaces of PV panels significantly degrades the access of solar radiation to them, and to prevent the loss of energy resulting from the dust accumulated on the surfaces of modules requires frequent cleaning of PV systems, its availability depends on the geographical location of solar plants [1]. There is a range of existing water pumping systems in Sharjah that rely on traditional and renewable energy sources like solar photovoltaic panels, mechanical types of windmills, diesel generators and wind turbines.…”
Section: Introductionmentioning
confidence: 99%